Time-driven activity-based costing for health care provider supply chains. Issue 2 (3rd April 2017) - Gonzalez, Martha; Nachtmann, Heather; Pohl, Edward
ABSTRACT: Health care providers currently operate in an environment of complex supply chains and increasing costs where approximately one third of hospital operating expenses are related to supplies. It is pertinent that health care providers have a clear understanding of their supply chain process costs. Knowing how these costs are driven and where opportunities for cost reduction exist can support health care provider supply chain (HPSC) efficiency. In this article, we present a time-driven activity-based costing (TDABC) supply chain cost methodology for health care providers. A TDABC management system can provide health care providers with valuable product and process supply chain cost information by investigating logistics activities, resource consumption, and time drivers. Our HPSC TDABC methodology is demonstrated in a case study conducted for the supply chain department of a 200-bed, not-for-profit hospital.